Corn Yield and Phosphorus Use Efficiency Response to Phosphorus Rates Associated With Plant Growth Promoting Bacteria - Pereira, Nathália Cristina Marchiori; Galindo, Fernando Shintate; Gazola, Raíssa Pereira Dinalli; Dupas, Elisângela; Rosa, Poliana Aparecida Leonel; Mortinho, Emariane Satin; Filho, Marcelo Carvalho Minhoto Teixeira (Frontiers in Environmental Science, 2020)
The use of plant growth promoting bacteria that can solubilize phosphorus (P) has shown potential to improve nutrient availability in grass crops such as corn (Zea mays L.) This study was developed to investigate if inoculation with Azospirillum brasilense, Bacillus subtilis or Pseudomonas fluorescens associated with P2O5 rates can improve phosphorus use efficiency (PUE) reflecting on greater corn development and yield. The field trial was set up in a Rhodic Hapludox under no-till system under Savannah conditions, in a completely randomized block design with four replicates. Treatments were tested in a full factorial design and included: i) five P2O5 rates (0 to 105 kg ha-1) and ii) four PGPB seed inoculation (Control – without inoculation, A. brasilense, B. subtilis or P. fluorescens). Inoculation was found to increase grain yield by 17.5% when B. subtilis was inoculated associated with 70 kg P2O5 ha-1 and by 34.7% when A. brasilense was inoculated with application of 105 kg P2O5 ha-1. In addition, inoculation with B. subtilis and A. brasilense were found to increase biomass and grain P uptake, number of grains per row, stem diameter, ear length and PUE. The results of this study showed positive improvements in P uptake as a result of B. subtilis and A. brasilense inoculation, with an increase of 86.9 and 40.6% on PUE, respectively; while the P. fluorescens inoculation were less evident. Further research should be conducted under biotic or/and abiotic conditions to better understand the role of PGPB, inoculated alone or in combination as the co-inoculated method.